THE ROLE OF ISLAMIC MICROFINANCE BANKS IN PROMOTING THE SOCIAL WELFARE: A CASE STUDY OF YOBE MICROFINANCE BANK - IBRAHIM, SHERIFF MUHAMMAD; MUHAMMAD, TIJJANI (Innovare Journal of Social Sciences, 2023)
The study assesses the Islamic Microfinance Bank’s role in promoting customers’ social welfare, using the newly developed products of Yobe Microfinance Bank to encourage inclusion and alleviate poverty in the Yobe communities. Yobe State is ranked bottom as the poorest in the region and scores low on human development and poverty alleviation. It indicates low education rates, poor implementation of government policies on poverty, and a high financial exclusion rate. The study adopted a qualitative approach using random sampling to collect data from customers of Yobe Microfinance Bank. Using the acceptability of the newly introduced sharia complaint products of Yobe Microfinance among the people in Yobe state, using the Structural Equation Modelling, 300 respondents completed the survey using a Likert scale. The study employed Structural Equation Modeling to analyze and test reliability and validity to provide accuracy of respondents’ information. The finding indicates the positive relationship between Islamic banking products and customer satisfaction. The study concludes that introducing and consistently managing Islamic products can improve social welfare and reduce poverty through financial inclusion in the state.